Roads in the deserts of Roman Egypt - Paprocki, Maciej (Oxbow Books, 2019)
Egypt under the Romans (30 BCE-3rd century CE) was a period when local deserts experienced an unprecedented flurry of activity. In the Eastern Desert, a marked increase in desert traffic came from imperial prospecting/quarrying activities and caravans transporting wares to and from the Red Sea ports. In the Western Desert, resilient camels slowly became primary beasts of burden in desert travel, enabling caravaneers to lengthen daily marching distances across previously inhospitable dunes. Desert road archaeology has used satellite imaging, landscape studies and network analysis to plot desert trail networks with greater accuracy; however, it is often difficult to date roadside installations and thus assess how these networks evolved in scope and density in reaction to climatic, social and technological change. 0Roads in the Deserts of Roman Egypt examines evidence for desert roads in Roman Egypt and assesses Roman influence on the road density in two select desert areas: the central and southern section of the Eastern Desert and the central Marmarican Plateau and discusses geographical and social factors influencing road use in the period, demonstrating that Roman overseers of these lands adapted remarkably well to local desert conditions, improving roads and developing the trail network. Crucially, the author reconceptualises desert trails as linear corridor structures that follow expedient routes in the desert landscape, passing through at least two functional nodes attracting human traffic, be those water sources, farmlands, mines/quarries, trade hubs, military installations or actual settlements